2010
DOI: 10.1016/j.jtcvs.2009.11.058
|View full text |Cite
|
Sign up to set email alerts
|

Repair of regurgitant bicuspid aortic valves: A systematic approach

Abstract: A systematic approach to bicuspid aortic valve repair yields good early and midterm results. Repair of bicuspid valves for aortic insufficiency is a feasible and attractive alternative to mechanical valve replacement in young patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
100
0
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(121 citation statements)
references
References 23 publications
8
100
0
13
Order By: Relevance
“…Nevertheless, although still far from being uniform among countries or even within the same institution, repair of the regurgitant bicuspid (BAV) or tricuspid (TAV) aortic valve has slowly evolved in recent years toward a more consistently characterized and more standardized armamentarium of strategies. [2][3][4][5][6][7] Several attempts to systematically characterize the mechanisms of AR in TAV or BAV that focus on relevance for surgical repair rather than on morphology have contributed to this evolution. 7,8 Lesions of the cusps and other components of the aortic root that contribute to AR and need to be surgically addressed singly or in combination are now better understood and described.…”
Section: Advantages Of Aortic Valve-sparingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, although still far from being uniform among countries or even within the same institution, repair of the regurgitant bicuspid (BAV) or tricuspid (TAV) aortic valve has slowly evolved in recent years toward a more consistently characterized and more standardized armamentarium of strategies. [2][3][4][5][6][7] Several attempts to systematically characterize the mechanisms of AR in TAV or BAV that focus on relevance for surgical repair rather than on morphology have contributed to this evolution. 7,8 Lesions of the cusps and other components of the aortic root that contribute to AR and need to be surgically addressed singly or in combination are now better understood and described.…”
Section: Advantages Of Aortic Valve-sparingmentioning
confidence: 99%
“…El Khoury and colleagues 2,7,9 have introduced a classification of AR that characterizes regurgitation mechanisms with the hope of clarifying the optimal surgical treatment strategy. Type I AR is defined as regurgitation in the presence of normal cusp mobility.…”
Section: Mechanisms Of Armentioning
confidence: 99%
“…At 5 years, freedom from recurrent regurgitation was high at 94±3%. Furthermore, in unadjusted analyses, patients undergoing a root procedure (remodelling or reimplantation) had a greater freedom from recurrent regurgitation compared to those undergoing subcommissural annuloplasty or sinotubular junction plication (95± 5%vs 80±6% at 5 years, p=0.03) [25].…”
Section: Bicuspid Aortic Valvesmentioning
confidence: 96%
“…The repair of bicuspid valves for AI was found to be a feasible and attractive alternative to mechanical valve replacement in young patients. 40) The most recent novel studies reported that BAV repair was likely to be safe and durable with low mortality, a low prevalence of reoperation, and good long-term survival. 41,42) Ozaki et al had recently developed a unique and novel technique for original aortic valve reconstruction with an autologous pericardium and described the surgical treatment of BAV with original aortic valve reconstruction using a harvested pericardium treated with 0.6% glutaraldehyde solution.…”
Section: Clinical Outcomes and Durability Of Bicuspid Aortic Valve Rementioning
confidence: 99%